Capital structure dynamics in Indonesia: Understanding the role of ROA in the relationship between firm age, size, and leverage - Meilita, Willi; Suseno, Giri; Sari, Nurmala (Institute of Computer Science (IOCS), 2024)
This study examines the dynamics of capital structure in Indonesia by exploring the role of Return on Assets (ROA) in mediating the relationship between firm age, size, and leverage usage. Employing a quantitative approach, the research analyzes panel data from 424 non-financial companies listed on the Indonesia Stock Exchange during 2019-2021. The analysis utilizes Partial Least Squares (PLS), emphasizing that the data does not need to be normally distributed and can accommodate small sample sizes. The findings indicate that ROA acts as a negative, albeit statistically insignificant, mediator in the relationship between both firm age and size with leverage. Despite theoretical frameworks like Pecking Order and Market Timing Theories suggesting explanatory mechanisms, the study reveals that ROA’s mediation is not robust enough to substantiate these theories. Consequently, the results suggest that other factors may be more pivotal in explaining the observed relationships. This study underscores the need for further research into how firm characteristics influence capital structure, particularly in emerging markets like Indonesia. It contributes to the theoretical and practical understanding of capital structure management, providing crucial insights for investors and managers.